Evolution of tyrosinemia type 1 disease in patients treated with nitisinone in Spain. Issue 39 (September 2019) - Couce, María Luz; Sánchez-Pintos, Paula; Aldámiz-Echevarría, Luís; Vitoria, Isidro; Navas, Victor; Martín-Hernández, Elena; García-Volpe, Camila; Pintos, Guillem; Peña-Quintana, Luis; Hernández, Tomás; Gil, David; Sánchez-Valverde, Félix; et al.
Abstract : Abstract: Treatment with nitisinone (NTBC) has brought about a drastic improvement in the treatment and prognosis of hereditary tyrosinemia type I (HT1). We conducted a retrospective observational multicentric study in Spanish HT1 patients treated with NTBC to assess clinical and biochemical long-term evolution. We evaluated 52 patients, 7 adults and 45 children, treated with NTBC considering: age at diagnosis, diagnosis by clinical symptoms, or by newborn screening (NBS); phenotype (acute/subacute/chronic), mutational analysis; symptoms at diagnosis and clinical course; biochemical markers; doses of NTBC; treatment adherence; anthropometric evolution; and neurocognitive outcome. The average follow-up period was 6.1 ± 4.9 and 10.6 ± 5.4 years in patients with early and late diagnosis respectively. All patients received NTBC from diagnosis with an average dose of 0.82 mg/kg/d. All NBS-patients (n = 8) were asymptomatic at diagnosis except 1 case with acute liver failure, and all remain free of liver and renal disease in follow-up. Liver and renal affectation was markedly more frequent at diagnosis in patients with late diagnosis ( P < .001 and .03, respectively), with ulterior positive hepatic and renal course in 86.4% and 93.2% of no-NBS patients, although 1 patient with good metabolic control developed hepatocarcinoma. Despite a satisfactory global nutritional evolution, 46.1% of patients showed overweight/obesity. Interestingly lower body mass index was observed in patients with good dietary adherence (20.40 ± 4.43 vs 24.30 ± 6.10; P = .08) and those with good pharmacological adherence (21.19 ± 4.68 vs 28.58 ± 213.79). intellectual quotient was ≥85 in all NBS- and 68.75% of late diagnosis cases evaluated, 15% of which need pedagogical support, and 6.8% (3/44) showed school failure. Among the 12 variants identified in fumarylacetoacetate hydrolase gene, 1 of them novel (H63D), the most prevalent in Spanish population is c.554–1 G>T. After NTBC treatment a reduction in tyrosine and alpha-fetoprotein levels was observed in all the study groups, significant for alpha-fetoprotein in no NBS-group ( P = .03), especially in subacute/chronic forms ( P = .018). This series confirms that NTBC treatment had clearly improved the prognosis and quality of life of HT1 patients, but it also shows frequent cognitive dysfunctions and learning difficulties in medium-term follow-up, and, in a novel way, a high percentage of overweight/obesity.